Spectroscopic studies on the thermodynamics of the complexation of trivalent curium with propionate in the temperature range from 20 to 90 °C - Skerencak-Frech, Andrej; Höhne, Stefanie; Hofmann, Sascha; Marquardt, Christian M.; Panak, Petra (Journal of solution chemistry, 2013)
The thermodynamics of the stepwise complexation reaction of Cm(III) with propionate was studied by time resolved laser fluorescence spectroscopy (TRLFS) and UV/Vis absorption spectroscopy as a function of the ligand concentration, the ionic strength and temperature (20-90 °C). The molar fractions of the 1:1 and 1:2 complexes were quantified by peak deconvolution of the emission spectra at each temperature, yielding the log10$$ K_{n}^{′ } $$values. Using the specific ion interaction theory (SIT), the thermodynamic stability constants log10$$ K_{n}^{0} (T) $$were determined. The log10$$ K_{n}^{0} (T) $$values show a distinct increase by 0.15 (n = 1) and 1.0 (n = 2) orders of magnitude in the studied temperature range, respectively. The temperature dependency of the log10$$ K_{n}^{0} (T) $$values is well described by the integrated van’t Hoff equation, assuming a constant enthalpy of reaction and $$ \Updelta_{\text{r}} C^°_{{p,{\text{m}}}} = 0, $$yielding the thermodynamic standard state $$ \left( {\Updelta_{\text{r}} H^°_{\text{m}} ,\Updelta_{\text{r}} S^°_{\text{m}} ,\Updelta_{\text{r}} G^°_{\text{m}} } \right) $$values for the formation of the $$ {\text{Cm(Prop)}}_{n}^{3 - n} $$, n = (1, 2) species.
Published: 12 January 2013
Gesehen am 03.02.2022